Nematic director reorientation at solid and liquid interfaces under flow SAXS studies in a microfluidic device - Silva, Bruno F B (Langmuir : the ACS journal of surfaces and colloids, 2015)
In this work we investigate the interplay between flow and boundary condition effects on the orientation field of a thermotropic nematic liquid crystal under flow and confinement in a microfluidic device. Two types of experiments were performed using synchrotron small-angle X-ray-scattering (SAXS). In the first, a nematic liquid crystal flows through a square-channel cross section at varying flow rates, while the nematic director orientation projected onto the velocity/velocity gradient plane is measured using a 2D detector. At moderate-to-high flow rates, the nematic director is predominantly aligned in the flow direction, but with a small tilt angle of ∼±11° in the velocity gradient direction. The director tilt angle is constant throughout most of the channel width but switches sign when crossing the center of the channel, in agreement with the Ericksen-Leslie-Parodi (ELP) theory. At low flow rates, boundary conditions begin to dominate, and a flow profile resembling the escaped radial director configuration is observed, where the director is seen to vary more smoothly from the edges (with homeotropic alignment) to the center of the channel. In the second experiment, hydrodynamic focusing is employed to confine the nematic phase into a sheet of liquid sandwiched between two layers of Triton X-100 aqueous solutions. The average nematic director orientation shifts to some extent from the flow direction toward the liquid boundaries, although it remains unclear if one tilt angle is dominant through most of the nematic sheet (with abrupt jumps near the boundaries) or if the tilt angle varies smoothly between two extreme values (∼90 and 0°). The technique presented here could be applied to perform high-throughput measurements for assessing the influence of different surfactants on the orientation of nematic phases and may lead to further improvements in areas such as boundary lubrication and clarifying the nature of defect structures in LC displays